Engaging pregnant individuals and healthcare professionals in an international mixed methods study to develop a core outcome set for studies on placenta accreta spectrum disorder (COPAS): a study protocol - Janet A Parsons; Rohan D’Souza; John C Kingdom; Jon F R Barrett; Susan E O’Rinn (BMJ Open)
Introduction Placenta accreta spectrum (PAS) disorder is a life-threatening condition that may result in serious maternal complications, including mortality. The placenta which is pathologically adherent to the uterine wall, places individuals at high risk of major haemorrhage during the third stage of labour. Current research reports on PAS disorder outcomes have highly variable levels of information, which is therefore difficult for investigators to aggregate to inform practice. There is an urgent need to harmonise data collection in prospective studies to identify and implement best practices for management. One approach to standardise outcomes across any health area via the use of core outcome sets (COSs), which are consensus-derived standardised sets of outcomes that all studies for a particular condition should measure and report. This protocol outlines the steps for developing a COS for PAS disorder (COPAS).Methods and analysis This protocol outlines steps for the creation of COPAS. The first step, a systematic review, will identify all reported outcomes in the scientific literature. The second step will use qualitative one-on-one interviews to identify additional outcomes identified as important by patients and healthcare professionals that are not reported in the published literature. Outcomes from the first two steps will be combined to form an outcome inventory. This outcome inventory will inform the third step which is a Delphi survey that encourages agreement between patients and healthcare professionals on which outcomes are most important for inclusion in the COS. The fourth step, a consensus group meeting of representative participants, will finalise outcomes for inclusion in the PAS disorder COS.Ethics and dissemination This study has obtained Research Ethics Board approval from Sunnybrook Health Sciences Centre (#2338, #1488). We will aim to publish the study findings in an international peer-reviewed OBGYN journal.Registration details COMET Core Outcome Set Registration: https://www.comet-initiative.org/Studies/Details/1127.PROSPERO registration number CRD42020173426.